On the move : a life - Sacks, Oliver, 1933-2015 (Alfred A. Knopf, 2015)
Physician and writer Oliver Sacks recounts his experiences as a young neurologist; his physical passions--weight lifting and swimming; his love affairs, both romantic and intellectual; his guilt over leaving his family to come to America; his bond with his schizophrenic brother; and the writers and scientists--Thom Gunn, A. R. Luria, W. H. Auden, Gerald M. Edelman, Francis Crick--who influenced him.